Successful Time Management : A Self-Teaching Guide - Ferner, Jack D. (GHQ, Rawalpindi Services Book Club, 2003)
From establishing goals and prioritizing to delegating effectively, this practical guide covers all aspects of time management. Charts, worksheets and graphs enable the reader to utilize time-saving technology to balance work, family and personal commitments.
Include Index
Keywords: Management -- Time study -- Time management